Improving access to psychological therapies (IAPT) for people with bipolar disorder: Summary of outcomes from the IAPT demonstration site. (December 2018) - Jones, Steven H.; Akers, Nadia; Eaton, Jayne; Tyler, Elizabeth; Gatherer, Amanda; Brabban, Alison; Long, Rita; Lobban, Fiona
Abstract: Access to structured psychological therapy recommended for bipolar disorder (BD) is poor. The UK NHS Improving Access to Psychological Therapies initiative commissioned a demonstration site for BD to explore the outcomes of routine delivery of psychological therapy in clinical practice, which this report summarises. All clinically diagnosed patients with BD who wanted a psychological intervention and were not in acute mood episode were eligible. Patients were offered a 10-session group intervention (Mood on Track) which delivered NICE congruent care. Outcomes were evaluated using an open (uncontrolled), pre-post design. Access to psychological therapy increased compared to preceding 6 years by 54%. 202 people began treatment; 81% completed >5 sessions; median 9 sessions (range 6–11). Pre-post outcomes included personal recovery (primary outcome), quality of life, work and social functioning, mood and anxiety symptoms (secondary outcomes). Personal recovery significantly improved from pre to post-therapy; medium effect-size ( d  = 0.52). Secondary outcomes all improved (except mania symptoms) with smaller effect sizes ( d  = 0.20–0.39). Patient satisfaction was high. Use of crisis services, and acute admissions were reduced compared to pre-treatment. It is possible to deliver group psychological therapy for bipolar disorder in a routine NHS setting. Improvements were observed in personal recovery, symptoms and wider functioning with high patient satisfaction and reduced service use. Highlights: We summarised outcomes of delivery of psychological therapy for bipolar disorder in clinical practice. Most people offered therapy accepted and completed it. Post therapy improvements were found for personal recovery and most secondary functional and symptom outcomes. It is possible to deliver effective psychological treatment for bipolar disorder in NHS settings.